Composition of biotite within the wushan granodiorite, jiangxi province, china: petrogenetic and metallogenetic implications (2014)
The Wushan skarn copper deposit is genetically associated with the Wushan granodiorite. In this study, we investigate the petrography and mineralogy of biotites within the Wushan granodiorite. We also determine the formation conditions of these biotites and discuss the significance of these minerals in terms of petrogenesis and mineralization. Electron microprobe analysis shows that biotites within the Wushan granodiorite are Magnesio-biotites that contain relatively high Mg and Ti concentrations and low Fe and Al concentrations. The ionic coefficient of AlVI in these biotites ranges from 0.03 to 0.19, with SFeO/(SFeO + MgO) ratios that range from 0.531–0.567 and MgO concentrations that range from 12.80–14.06 wt%. These results indicate that the Wushan granodiorite is an I-type granite. The Wushan biotites crystallized at temperatures (T) of 720°C–750°C, with oxygen fugacity (fO2) conditions of –11.6 to –12.5 and pressures (P) of 0.86–1.03 kb. These conditions are indicative of a crystallization depth (H) of 2.84–3.39 km. These data also indicate that the Wushan granodiorite developed under conditions of high temperature and high oxygen fugacity, suggesting that the Wushan granodiorite is prospective for magma-hydrothermal mineralization and that this granodiorite probably contributed to the formation of the Wushan skarn copper deposit. ResumenEl depósito de skarn cuprífero de Wushan está asociado genéticamente con la granodiorita de Wushan. En este estudio se investiga la petrografía y mineralogía de biotitas de la granodiorita de Wushan. Se determinan también las condiciones de formación de estas biotitas y se discute la significación de estos minerales en términos de petrogénesis y mineralización. Un análisis de microsonda a electrones muestra que las biotitas de la granodiorita de Wushan son biotitas de magnesio que contienen altas concentracionesrelativas de Mg y Ti y bajas de Fe y Al. El coeficiente icónico de AlVI en estas biotitas oscila entre 0,03 y 0,19, con índices SFeO/(SFeO + MgO) que oscilan entre 0,531-0,567 y concentraciones de MgO que van desde 12,80 a 14,06 wt%. Estos resultados indican que la granodiorita de Wushan es de granito tipo I. Las biotitas de Wushan se cristalizaron a temperaturas (T) de 720°C–750°C, con condiciones de fugacidad del oxígeno (fO2) de -11,6 a -12,5 y presión (P) de O,86 a 1,03 kb. Estas condiciones indican una profundidad de cristalización (H) de 2,84-3,39 kilómetros. Los datos también indican que la granodiorita de Wushan se desarrolló bajo condiciones de alta temperatura y alta fugacidad de oxigeno, lo que sugiere que la granodiorita de Wushan tiene potencial para la mineralización magmática-hidrotérmica y que esta granodiorita probablemente contribuyó a la formación del depósito de skarn cuprífero de Wushan.